Politics of reproduction: a view from Israel on the Dobbs decision - Carmel Shalev (BMC, 2023)
Abstract Background This opinion piece looks at the recent decision of the United States Supreme Court in Dobbs v. Jackson Women's Health Organization and then compares the law on abortion in the USA to the law in Israel on reproductive medicine in general. The Dobbs decision validated a Mississippi state law that restricted access to abortion, while overruling the landmark precedent of Roe v. Wade on women's constitutional right to safe abortion. It declared that the US constitution does not confer upon women any right to abortion, whether pre- or post-viability, sending shockwaves throughout the world. It also had an immediate effect on women's reproductive health in the US. Main body Women's right to reproductive freedom and to make decisions about their lives and their bodies is key to their hard-won equality. Still, abortion remains in ongoing controversy worldwide with legal barriers that impact upon the most vulnerable. In Israel, abortion is relatively available, accessible, affordable, and acceptable, in both law and practice. This is because of the lenient and nuanced stance of rabbinical authorities in the Jewish law tradition. This stance, together with Israel's post-Holocaust biblical culture of "be fruitful and multiply", also underlies its high rates of medically assisted reproduction for the treatment of infertility, including preimplantation genetic diagnosis of fertilized eggs. Women's bodies mediate all these repro-genetic technologies, in most cases for the benefit of others, not because of their own health needs. There is also concern about global practices and market forces that objectify women's bodies, exploit women and are harmful to their health, wellbeing, and dignity, carrying on outdated patriarchal patterns. Conclusion Reproductive health policy ought to be based on an ethic of care and responsibility first and foremost for the women, as well as the children they choose to bring to life, in the spirit of the Jewish tradition that her life is of greater value than the fetus'. Women deserve control of their bodies and their lives and respect for the choices they make to the best of their judgment, which when it comes to abortion are mostly hard ones. They have a right to reproductive choice, freedom, autonomy, and dignity. The views expressed in this perspective are those of the author.